STUDI KEPUASAN TAMU HOTEL: PENGARUH HARGA, FASILITAS DAN KUALITAS PELAYANAN SEBAGAI PREDIKTOR DI HOTEL TENTREM SEMARANG - Rizky Hadi Purnomo; Andhi Supriyadi (LPSDI Bina Patria, 2024)
The purpose of this research is to find out and explain how guest satisfaction at the Tentrem Hotel Semarang is influenced by price, facilities and service quality. The research was conducted through questionnaires and sample documents given to 95 respondents. It is hoped that the research findings will provide useful information for hotel management and overnight guests. Descriptive analysis and quantitative statistics are used in processing the data obtained. Quantitative analysis uses multiple regression to measure the influence of the independent variable on the dependent variable. Before the analysis was carried out, validity, reliability and requirements tests were carried out. The results of the regression analysis showed that facilities, price and service quality partially influenced guest satisfaction at the Tentrem Hotel Semarang. On the other hand, facilities, price and service quality also have a joint influence on guest satisfaction.